Development and Performance Evaluation of Animal Drawn Garlic Digger - Kumar, Manish; Badegaonkar, U. R.; Din, M. (Journal of Agricultural Engineering, 2017)
An animal drawn garlic digger, especially for small and marginal farms, was developed. Six types of digger blades with varied width and nose angles were evaluated for digging of garlic plants. The digger was operated at 16 % (d.b.) soil moisture content and cone index of 1350 kpa within soil profile 0-150 mm. The draft requirement of 650 mm wide blades was 30% higher than the pulling capacity of selected pair of bullocks. Blades of 550 mm of radius of curvature and 700 mm wide curved type with radius of curvature 700 mm had 86% efficiency, and required less draft with bullock fatigue score of 12. The fatigue score of blade of same width with 170° and 150° nose angle were 18 and 16, respectively. Field capacity of the digger was found to be 0.12 ha.h-1, and almost 25 times higher than that of manual digging. The average garlic damage was in the range of 3.62–5.40% for selected blades. The animal drawn garlic digger saved 75% cost and 44.8% energy as compared to the traditional method of manual digging.